A review of Menopaysal symptoms management with herbal remedies - Parhizkar, Saadat; Abd Latiff, Latiffah; Dollah, Mohamad Aziz; Syed Hassan, Syed Tajuddin; Ibrahim, Rashid; Hanachi, Parichehr (EuroJournals, 2008)
Background: Women are frequent users of complementary and alternative medicine(CAM)therapies for menopausal symptoms in many countries. Therapies of choice were herbal remedies, chiropractic, and meditation. Recently, dietary supplements and foods containing phytoestrogens have become increasingly popular, despite the lack of data from clinical trials. Purpose: To review randomized, controlled trials of herbal remedies for menopausal symptoms in order to better inform practice and guide future research. Data Sources: MEDLINE and Cochrane Library database (1980 February 2008) were searched for relevant trials that provided data on treatment of menopausal symptoms using 1 or more herbal remedies. Study Selection: All English language, controlled trials and meta-analyses comparing a botanical with placebo or control for relieving menopausal symptoms. Data Extraction: All eligible trials were identified, subjected to inclusion and exclusion criteria, reviewed, and abstracted into evidence tables. Data Synthesis: From 3119 identified abstracts, 85 trials met inclusion criteria, including 50 trials of isoflavones, 15 trials of Black Cohosh, 8 trials of combination of botanicals and other studies were belong to the other herbs. Conclusion: Although individual trials suggest benefits from certain therapies, data were insufficient to support the effectiveness of any botanicals in this review for the management of menopausal symptoms. Many of these potential therapies warrant further study in trials with rigorous scientific designs to determine benefit and safety.